THE USE OF COMIC PHRASEOLOGICAL UNITS IN CULTURAL AND SOCIAL CONTEXTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article explores the use of comic phraseologisms within various cultural and social contexts, focusing on their significance in communication, humor, and identity construction. Comic phraseologisms, which are fixed expressions conveying humor, play a crucial role in reflecting cultural values, social norms, and collective experiences. By analyzing examples from both Uzbek and English languages, the study highlights how these expressions serve not only as linguistic tools but also as instruments of social cohesion and cultural commentary. The research employs a contrastive approach, examining the nuances of comic phraseologisms in different cultural settings and their impact on interpersonal interactions. Through qualitative analysis, the article underscores the interplay between language and culture in shaping humor and facilitating social connections.